The Role of the Principal in Improving the Quality of Education in the Society 5.0 Era - Deding Ishak (Budapest International Research and Critics University, 2022)
The quality possessed by a school is primarily determined by the school principal’s leadership, especially in the era of globalization with the existence of society 5.0. Understanding how to be a good and faithful principal can help the principal’s leadership become more effective. Of course, it is necessary to have competencies possessed by school principals to lead schools better and support their professional performance. This research was conducted using a qualitative approach. The study results indicate a change in school quality as a result of the quality of the principal. Then, it was also found the role of the principal in the school and its role in the quality of education.